Systematic Literature Review (SLR): Transformasi sektor Pertanian Bagi Pembangunan Ekonomi di pedesaan Indonesia - Chudriana Putri, Rafika; Harahap , Isnaini; Nawawi , Zuhrinal (Jurnal Paradigma Ekonomika, 2024)
Indonesia is a developing country. One way to build a country's national economy is by developing the agricultural sector and rural areas properly. This study aims to determine the Transformation of the Agricultural Sector for Economic Development in Rural Indonesia with a Systematic Literature Review paradigm approach in journals that have been published since 2017 to 2023. The results obtained are that the Transformation of the agricultural sector must be carried out immediately because the interest of the Indonesian people in Farming is still low. The conversion of land functions and the age of the rural population are mostly elderly are the impetus for the agricultural sector to transform immediately. Transformation needs to be carried out because technological developments in the agricultural sector are not as fast as the development of other technologies, for example in the industrial sector. This requires government support through regulations that facilitate access to capital, low interest rates, digital markets, and the development of agricultural technology. Agricultural transformation can drive Indonesia's rural economic development.